Feudalism versus capitalism: the changing representation of Lombok in Nadira Khalid's novel Ketika Cinta Tak Mau Pergi - HD, Dharma Satrya (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article aims to explain the changes in Lombok representation in Ketika Cinta Tak Mau Pergi (When Love Refuses to Leave) novel by Nadira Khalid. To explain this, this article uses representation theories and methods that combine semiotic and discourse models. Lombok is represented as part of Java, as the literary language of Lombok is Javanese. Through literature, the Sasak people of Lombok have gained knowledge of feudalism, a social system that remains common until today. Java interpellates Sasak as a feudal subject. Nobility maintains a system of feudalism and perwangsa dengan jamaq carrying the spirit equality. Nobles dominate the production of culture, especially Sasak Literature, through the publication of West Nusa Tenggara Barat historical monograph. The novel Ketika Cinta Tak Mau Pergi depicts capitalism as an alternative to feudalism. This can be seen in the novel's narrative, which follows a noble family that must migrate to Sumbawa after their village is purchased by a company that seeks to build a factory on the land. The novel shows the Sasak people prefer becoming factory workers over farming, and as an implication of capitalism the island experiences economization process. However, both worldviews pose obstacles to the love of the main characters Lalu Kertiaji and Sahnim. Romanticism, thus, is seen as offering an alternative to both these views.